STRATEGI PEMBANGUNAN EKONOMI BERBASIS KOMUNITAS DI KOTA MADIUN - Ramadhan Prasetya Wibawa; Dwi Nila Andriani (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Community-based economic development strategy is an alternative in human-cantered development process related to good community management, so it can be the answer to development challenges such as social imbalance, poverty, poor environment, lack of community participation.This research was conducted in Madiun with sources of informants who have been established by using as informants in this research community in Madiun. Data collection is done by interview, documentation and field observation. The data collected are analyzed by an interactive model analysis. The results of the study showed that community-based economic development strategy involves not only the material physical and financial aspects but also involving broader aspects such as social, cultural, economic, to institutional and ecological regulations. Improving efforts have the potential to increase the capacity and potential of developing and participatory community members for their responsibilities through workshops, brainstorming, group discussions, coupons, trainings.